Three-dimensional spatial structure and heterogeneity characterization of #5 coal of Shanxi Formation in eastern Ordos basin - Yunhe, Shi; Hui, Zhang; Bo, Pan; Xueyuan, Jing; Xiaowei, Du; Xiaohu, Zhou (Frontiers in Energy Research, 2024)
Based on macroscopic qualitative observation, microscopic quantitative analysis, low-temperature adsorption, high-pressure mercury intrusion and three-dimensional CT scanning, the spatial structure and heterogeneity of the #5 coal from the eastern Ordos Basin, Shanxi Formation, are quantitatively characterized. The following observation were studied: 1) The main body of the #5 coal was intact structural coal seam, with the density of cleats gradually increasing from north to south. 2) The microscopic composition of the #5 coal is dominated by desmocollinite, which contains small amounts of inertinite and inorganic minerals, with the inorganic component mainly composed of carbonate rocks and a small amount of clay. The carbon content and the content of its inorganic minerals in the #5 coal gradually decrease toward the inner basin, caused by transport distance and depositional environment. 3) At the micrometer scale, no significant pores were observed, and the #5 coal bed is primarily composed of micro-mesopores smaller than 40 nm, with a small number of 50∼100 nm macropores. Simultaneously, micro-fractures in the coal bed were well developed; by using mercury intrusion data of the bimodal feature of the pore throat, indicates the coexistence of micrometer-scale micro-fractures and nanometer-scale mesopores within the coal, with pronounced differences and interconnected complexity. 4) The porosity and permeability of microfractures, as well as the number of microfracture bars and permeability, indicate that the connectivity of coal bed is primarily caused by the microfracture system. By reconstructing the three-dimensional spatial structure of the #5 coal through multiple tests, the heterogeneous characteristics are quantitatively characterized.